Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1990
DOI: 10.1115/90-gt-027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of the Vortex Development Downstream of a Lobed Forced Mixer

Abstract: An experimental study was conducted to investigate the mixing processes downstream of a forced mixer. A forced mixer generates large scale, axial (stirring) vorticity which causes the primary and secondary flow to mix rapidly with low loss. These devices have been successfully used in the past where enhanced mixing of two streams was a requirement. Unfortunately, details of the mixing process associated with these lobed forced mixers are not well understood. Performance sensitivity to design variables has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 5 publications
5
30
1
Order By: Relevance
“…It indirectly indicated that the vortices breakdown induced numerous smallscale turbulent spots. 13 The vortices' interaction, especially their breakdown, was also one of the most important factors for accelerating the jet mixing. In addition, both the entrained ambient and separation bubble on center-body caused the high TKE fluid in the corresponding area.…”
Section: Baseline Casementioning
confidence: 99%
See 2 more Smart Citations
“…It indirectly indicated that the vortices breakdown induced numerous smallscale turbulent spots. 13 The vortices' interaction, especially their breakdown, was also one of the most important factors for accelerating the jet mixing. In addition, both the entrained ambient and separation bubble on center-body caused the high TKE fluid in the corresponding area.…”
Section: Baseline Casementioning
confidence: 99%
“…With the aggravation of entrainment, the normal vortices broke down at the streamwise vortices cores, as indicated by ''BD'' at x ¼ 1.0D plane in Figure 5(b). The vortices breakdown produced numerous small-scale turbulent spots, 13 and thus played very important role in accelerating the jet mixing. Conversely, this process enhanced streamwise vortices dissipation as well, which was shown by the sharp decreasing streamwise vorticity at streamwise vortex cores in x ¼ 1.0-2.0D planes.…”
Section: Baseline Casementioning
confidence: 99%
See 1 more Smart Citation
“…The streamwise vortices were reported to interact within a small distance downstream of the mixer trailing edge, but remain the largest scale fiow structure for three to ten lobe wavelengths downstream. Further investigations on the fundamental mechanism of mixing enhancement were carried out either experimentally or numerically by a lot of authors (such as Eckerle et al [11], McCormick and Bennett [12], Tsui and Wu [13], Glauser et al [14], Yu and Yip [15], Hu et al [16], etc. downstream of a lobed mixer were explained by McCormick and Bennett [12].…”
Section: Introductionmentioning
confidence: 99%
“…Effective mixing is accomplished through the generation of large scale axial vorticity. This is achieved by merging the two streams after they have been given moderate absolute but strong relative secondary flow components as a result of their passage over opposite sides of a gently transitioned planar-to-threedimensional surface, as described by Werle et al [5,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%